The Mapping of Resources and Development Potentials of Food-Secure Region in Kupang District, Province of Nusa Tenggara Timur - Pertiwiningrum, Ambar (2017)
Indonesia Food Sustainability and Vulnerability Assessment (FSVA) 2015 by the World Food Programme (WFP) categorized Province of Nusa Tenggara Timur as severely vulnerable to food-insecurity (priority 1). The aim of this program was to develop partial and spatial map of current condition, problems, threats, potentials, and strategic policies to develop food security in this area. The program was focused on Kupang district, Province of Nusa Tenggara Timur, through: 1) literature study; 2) identification and mapping of natural resources; 3) Focus Group Discussion; 4) field trip and data collection; 5) data analysis; 6) development of program; 7) workshop. Kupang district had three sub-districts that were most vulnerable to food insecurity (priority 1), namely Semau, South Semau, and Takari. The determining factors of vulnerability to food-insecurity were: (1) high poverty rate, (2) high prevalence of underweight among children, and (3) low access to clean water. The characteristic of the hilly areas in Kupang is dry-land on karst region with very low land-productivity. The limiting factors are low rainfall, low water availability, high temperature, low moisture and low fertility. Livestock were still raised traditionally on natural pastures. Some of the programs needed to enhance food-security in Tanini village are: (1) Improvement of land productivity, including infrastructure, facilities for intensive livestock farming systems, and optimization of dry land's potential; (2) Water management trough the construction of water reservoirs and the preservation of watershed and groundwater basins; (3) Capacity building for communities including farmers, the education on food consumption and processing, society empowerment by improving soft skills and hard skills. The analysis and estimation of World Food Programme showed that after intervention, the composite score of Kupang district changed from 91.18 (priority 3) to 66.54 (priority 5). The map of food-insecurity was ideal as a reference in planning an effective and efficient program.